The spread of Islam throughout the world - El Hareir, Idris, 1945-; Mbaye, Ravane (Different aspects of Islamic culture ;, 2011)
"Islamic culture, which is still vigorous in spite of its great antiquity, set out to develop side by side a vision of the individual and of the universe, a philosophy and an art of living that can be seen in the impressive remains of its heritage that is an essential part of the whole of humankind's. Halted for a time by adverse historical conditions, this culture none the less found the strength within itself to re-emerge. Its fidelity to its roots does not prevent it from keeping up with the times and participating in contemporary forums and the stirring dialogue of cultures. This series of volumes on the manifold facets of Islamic culture is intended to acquaint a very wide public with such matters as: the theological bases of the faith and principles that constitute the bedrock of the overall structure; the status of the individual and of society in the Islamic world; the expansion of Islam since the Revelation: the Arab, Asian, African and European spheres espousing the new faith and the way in which the rights of converted peoples have been upheld; the vital contribution of Islamic civilization to the adventure of human knowledge in science and technology; the educational and cultural manifestations of Islamic civilization in literature, the visual arts and architecture; finally, Islam today between loyalty to its past and the inescapable conquest of modernity."--Publisher's website.